Self-healing of fly ash-based geopolymers through the biomineralization of biochar-immobilized pure- and co-cultures of bacteria - Doctolero, Jadin Zam S. (Animo Repository, 2021)
A sustainable solution for crack maintenance in geopolymers is necessary if they are to be the future of modern green construction. This study thus aimed to develop self-healing geopolymers and to prove that self-healing indeed occurred. The main objective was achieved in a three-part methodology. First, three ureolytic bacteria, namely Bacillus subtilis, Bacillus sphaericus, and Bacillus megaterium, were examined for their potential to act as a healing agent. Both B. subtilis and B. sphaericus were observed to demonstrate the capability to precipitate the minerals needed for crack repair. Second, immobilization and co-culturing of bacteria were tested to determine their effect on the healing efficiency of the geopolymers and to obtain the optimal parameters that would yield the maximum response. The immobilizing material used was rice-husk biochar, and the co-cultures were made by growing B. sphaericus and B. thuringiensis. Weekly ultrasonic pulse velocity measurements were taken over a 28-day healing period to non-destructively quantify the changes in the strength or quality of the geopolymers. The results show that using co-cultured bacteria significantly improved the healing efficiencies of the specimens. This was primarily due to the increased number of nucleation sites for the precipitation of crack-sealing materials and the formation of biofilms to enhance the bacteria’s viability in the geopolymers. On the other hand, biochar concentration was found to weakly affect the healing efficiencies, but a peak response was observed between 0.3-0.4 g/mL. Aside from the observed improvements in the strength or quality of the geopolymers, crack sealing was also evident. The maximum crack width sealed was 0.65 mm. Through SEM-EDX and FTIR analyses, the precipitates in the cracks were identified to be mainly calcite, the trigonal polymorph of CaCO3. It was likewise proven through FTIR analysis that the specimens made were indeed geopolymers. For that reason, along with the evidences of crack sealing and strength restoration which are crucial indicators of self-healing, it suffices to call the innovative material developed as biogeopolymers. With further tests on their mechanical properties and applications, they could potentially rival the well-studied self-healing bioconcrete and truly be the future of modern green construction.